تأثير تدريب برامج ترجمة القرآن في إستعاب المفردات - Azhari, Saefullah; Syaifudin, Mochamad; Andriani, Liziyah; Safitri, Intan; Kanafillah, Abdurrahman (Prosiding Konferensi Nasional Bahasa Arab dan Pembelajarannya di Era Milenial, 2022)
We already know that Arabic is very important for us and all Muslims. Because the Al-Qur’an and Al-Hadith are guidelines for Muslims who also use Arabic. It should be remembered that actually learning Arabic is not a difficult thing if in learning it uses the right and easy method. Here the Al-Qur’an Translation Training Program becomes very important, because by using this method, learning Arabic becomes easier and shorter without spending a long time. The problem in this article aims to determine the extent of the influence of the Al-Qur’an translation training program in mufrodat learning. We can learn Arabic vocabulary in different ways, and one of the ways it can be used is to learn Arabic vocabulary by practicing Quran translation. In this case, the Quran translation training program can have a positive effect on improving vocabulary learning.